Antioxidant Activity Test for Button Mushroom (Agaricus bisporus) Ethanol Extract Using The FRAP Method (Ferric Reducing Antioxidant Power) - Suhaenah, Asriani; Baits, Muzakkir; Ismail, Normawati (Faculty of Pharmacy, Universitas Muslim Indonesia, 2023)
Button mushrooms (Agaricus bisporus) are plants that contain phenols as antioxidants. Antioxidants are electron donor or reductant compounds. These compounds have a small molecular weight but are able to inhibit the development of oxidation reactions by preventing the formation of radicals. phenol is the main antioxidant component found in Agaricus bisporus extracts. The aim of this research is to determine the antioxidant activity value of button mushroom ethanol extract (Agaricus bisporus) using the method of ferric reducing antioxidant power (FRAP). This research uses the maceration method as an extraction process using 96% ethanol. The resulting filtrate was concentrated with a vacuum rotary evaporator to produce a thick extract. Antioxidant testing was carried out using the FRAP method with a reagent solution of potassium feryricide, phosphate buffer pH 6.6 tricloroacetic acid (TCA), aquadest, and iron 3 chloride (FeCl3). Samples were analyzed using a UV-Vis spectrophotometer at a wavelength of 725 nm using quercetin as a standard solution. The results showed that the antioxidant activity value of the button mushroom ethanol extract (Agaricus bisporus) with the FRAP method was 3.847 mg QE /g extract.